Vacation Notes in Cromar, Burghead, and Strathspey: Including Notice of one of the Supposed Burial-Places of St Columba (Proceedings of the Society of Antiquaries of Scotland, 1875)
This article describes some of the sites of archaeological interest that the author encountered in Aberdeenshire and Moray in 1873. He describes the sites as he found them and then extrapolates on the local folklore about them and any historical background he researched while writing up his paper. Some of the other topics he covers include the location of St Columba’s burial, religious or superstitious healing traditions in the area, extracts from parish records that relate to the tradition of burning the clavie, and the religious implications of some of the stone monuments in the north-east.